2000
DOI: 10.1034/j.1399-0012.2000.140405.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐benefit analysis of a clinical pharmacist‐managed medication assistance program in a renal transplant clinic

Abstract: A clinical pharmacist-managed medication assistance program in a renal transplant clinic produced substantial cost savings over this 1-year study period. For each dollar spent in pharmacist's time, a minimum of $4 was returned to the institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…14 Chisholm et al indicated that use of PAPs resulted in cost avoidance of between $69,000 and $125,000 in atransplant clinic in auniversity teaching hospital for the 1998 calendar year. 15 Coleman et al reported net savings of $57,000 over 6months for indigent inpatients in aConnecticut hospital. 16 As Clay et al documented in an article in ap revious issue of JMCP, PAPs aren ot without costs.…”
Section: ■■ Pharmaceutical Patient Assistance Programs: Don't Look a mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Chisholm et al indicated that use of PAPs resulted in cost avoidance of between $69,000 and $125,000 in atransplant clinic in auniversity teaching hospital for the 1998 calendar year. 15 Coleman et al reported net savings of $57,000 over 6months for indigent inpatients in aConnecticut hospital. 16 As Clay et al documented in an article in ap revious issue of JMCP, PAPs aren ot without costs.…”
Section: ■■ Pharmaceutical Patient Assistance Programs: Don't Look a mentioning
confidence: 99%
“…Most of the available research has been limited to estimation of the short-term, direct costs of operating PAPs from the health carei nstitution' sp erspective. [14][15][16]18,19 Most researchers have focused on the costs of pharmacists, technicians, and other employees-such as social workers or patient registration technicians-employed to manage the process of applying for and dispensing PAPd rugs. For the most part, these studies have not included valuation of physician' st ime, overhead costs to the institution, or patients' time.…”
Section: ■■ Pharmaceutical Patient Assistance Programs: Don't Look a mentioning
confidence: 99%
“…Pharmacist-coordinated PAPp rograms in various settings have demonstrated net cost-savings to justify the higher pharmacy personnel costs. [6][7]11,16 Third, medication deliverym ay take 2t o6w eeks, so other means to bridge with an accessible and affordable therapeutically equivalent alternative may be necessaryw hile waiting. This is ap otential area for medication errors since patients are at risk of duplicating drug therapies if they do not receive proper counseling to discontinue the bridge medication.…”
mentioning
confidence: 99%
“…17 Examples of cost-savings from the establishment of PAPs have been demonstrated in ar enal transplant clinic (a minimum of $4 was returned to the institution for $1 spent in the pharmacist' stime). 6 Additionally,aPAP at amedical center clinic resulted in cost savings of $237,985 over 6months, yielding abenefit-to-cost ratio of 2.2:1. 16 Nykamp and Ruggles reported that maintaining adherence to needed medications improves caref or underserved patients and leads to decreased health caree xpenditures.…”
mentioning
confidence: 99%
See 1 more Smart Citation